Features of the clinical course and treatment of anaphylaxis in children in the Ryazan region according to survey data - E. V. Stezhkina; N. A. Belykh; A. I. Agapova; D. I. Suleymanova; A. N. Belyaeva (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2024)
Anaphylaxis is a life-threatening systemic hypersensitivity reaction with the rapid development of critical changes in hemodynamics and /or disorders of the respiratory system, which can lead to death. Despite the trend towards the spread of anaphylaxis among children, there are difficulties in monitoring statistical data, since there is no generally accepted cipher "Anaphylaxis" in the ICD-10, and designations from allergic urticaria to anaphylactic shock appear as a diagnosis. Epidemiological studies on anaphylaxis in the Russian Federation are isolated, so the assessment of data from each region is relevant.Objective: to study the clinical features and medical care for anaphylaxis in children of the Ryazan region in real clinical practice.Materials and methods: A retrospective analysis of medical documentation was carried out in 300 children who had suffered an "acute allergic reaction" over the past 5 years, followed by a telephone survey of patients' parents about the disease, and based on the clinical criteria for the diagnosis of anaphylaxis presented by the World Organization of Allergists (WAO) in 2020 and in the Federal Clinical Guidelines for the Diagnosis and Treatment of anaphylaxis, 57 patients were selected for anaphylactic shock of the Russian Federation in 2022, whose data were compared in a spreadsheet and analyzed using SPSS V24.0, including descriptive statistics.Results: It was revealed that the average age of first-time anaphylaxis is 3.5 years. Clinical manifestations from the skin and mucous membranes were present in 67.2 % of patients, symptoms from the respiratory system in 11.8 % of cases. The leading trigger for the occurrence of anaphylaxis in children is the nutritional factor (n = 27 (40 %), (χ2 = 4.56; p = 0.033)). In 29 % of cases, the causally significant allergen remained unknown. The most common drugs in the treatment of anaphylaxis in real clinical practice were glucocorticosteroids (n = 48 (84.2 %)) and antihistamines of the first and second generation (n = 47 (82.5 %)). The frequency of epinephrine use was only 3 cases (5 %).Conclusion: The epidemiological study of anaphylaxis in the Ryazan region was a pilot project for our region. It showed difficulties both in the organization and in the interpretation of the data obtained. According to preliminary results, food allergy is a frequent trigger of anaphylaxis in children of the Ryazan region. Regional studies of anaphylaxis in children in real clinical practice make it possible to identify not only the features of this urgent pathology, but also to note the problems of providing primary medical care in order to improve it. Further study of population models of anaphylaxis, apparently, should be based on the creation of a unified questionnaire of the pediatric community, following the example of the ISAAC questionnaires or the creation of registers, which will more accurately help determine the true prevalence of anaphylaxis, determine the need to identify anaphylactogenic relevant molecules in the pediatric population, and improve the provision of assistance to children with these conditions.